Peripheral arterial disease: Changes in clinical outcomes and therapeutic strategies in two cohorts, from 2002 to 2008 and from 2008 to 2014. A population-based study. (November 2018) - Baviera, Marta; Bertelè, Vittorio; Avanzini, Fausto; Vannini, Tommaso; Tettamanti, Mauro; Fortino, Ida; Bortolotti, Angela; Merlino, Luca; Roncaglioni, Maria Carla
Background: The aim of our study was to evaluate whether treatments for peripheral artery disease changed in two different cohorts identified in 2002 and 2008, and whether this had an impact on mortality and major clinical outcomes after six years of follow-up. Methods: Using administrative health databases of the largest region in Northern Italy, we identified patients admitted to hospital for peripheral artery disease in 2002 and 2008. Both cohorts were followed for six years. All cause death, acute coronary syndrome, stroke and major amputations, cardiovascular prevention drugs and revascularization procedures were collected. Incidence of events was plotted using adjusted cumulative incidence function estimates. The risk, for each outcome, was compared between 2002–2008 and 2008–2014 using a multivariable Fine and Gray's semiparametric proportional subdistribution hazards model. Results: In 2002 and 2008, 2885 and 2848 patients were identified. Adjusting for age, sex, Charlson comorbidity index and severity of peripheral artery disease we observed a significant reduction (in 2008 vs . 2002) in the risk of acute coronary syndrome (28%), stroke (27%) and major amputation (17%). No change was observed in the risk of death. The percentages of patients with peripheral artery revascularizations, during the hospital stay, increased: 43.8% in 2002 vs . 49.0% in 2008, p < 0.001. From 2002 to 2008 there was a significant absolute increase in the prescription of lipid-lowering drugs (+18%), antiplatelets (+7.2%) and angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (+11.8%), p < 0.001. Conclusions: In six years of follow-up we observed a reduction in risk of major cardiovascular events in 2008–2014 in comparison with the 2002–2008 cohort. Increasing use of revascularization interventions and cardiovascular prevention drugs could have contributed to the better prognosis.